A study on neurodevelopmental outcome and its associated risk factors in very low birth weight babies in a tertiary care teaching hospital in Kolkata - Sur, Somen; Das, Subhasis; Masani, Soumitra (Asian Journal of Medical Sciences, 2016)
Background: Very low birth weight babies are very fragile in nature and usually undergone through stormy neonatal period, which affects significantly their neurodevelopmental outcome in long term basis. Aims and Objectives: 1. Assessment of neurodevelopmental outcome in very low birth weight (VLBW) babies at 12 month corrected gestational age. 2. Study of risk factors associated with such outcome. Materials and Methods: VLBW babies without any major congenital anomaly were included in this study. They were followed up in high risk clinic upto 12 month corrected gestational age. In follow up visits, assessment of tone was done by Amiel Tiesonmethod and 180 degree flip test. Developmental screening was done by Denver Developmental Screening Test (DDST II).Data obtained from this study were entered in Microsoft Excel and subsequently analysed with the help of Epi Info (TM) 3.5.3 software. Results: 24.4% among the study population showed neurodevelopmental abnormalities. Of them, 22.2% VLBW infants had muscle tone abnormality; 15.6% were suspect in gross motor development, 8.9% were suspect in fine motor, 11.1% were suspect in personal – social and 8.9% were suspect in language development, which were statistically significant. On assessment of risk factors, it was found that low birth weight, prematurity, non-use of antenatal corticosteroid, hypoglycaemia, intraventricular haemorrhage, sepsis, jaundice, mechanical ventilation, intra uterine growth retardation were significantly associated with various strata of neurodevelopmental outcome. Conclusion: VLBW babies are very prone to develop neurodevelopmental complications. Taking proper care regarding above said risk factors can reduce such complications. Also these babies should follow up properly to detect complication/s at earliest, and take “early intervention’’ steps. Asian Journal of Medical Sciences Vol.7(5) 2016 61-69